Treatment of idiopathic scoliosis with conservative methods based on exercises: a systematic review and meta-analysis - Dimitrijević, Vanja; Rašković, Bojan; Popović, Miroslav; Viduka, Dejan; Nikolić, Siniša; Drid, Patrik; Obradović, Borislav (Frontiers in Sports and Active Living, 2024)
To systematically assess the effect size of conservative methods based on exercise for respondents with idiopathic scoliosis.This study was developed in accordance with the PRISMA guidelines. PubMed, Cochrane Library, Web of Science, and Google Scholar databases were searched in May 2023.The key search terms were: "Idiopathic scoliosis", "Adolescent idiopathic scoliosis", "Cobb angle", "Angle of trunk rotation", "Quality of life", "Schroth method", and "Core stabilization exercises". Risk of bias was assessed for each randomized trial using the Cochrane Risk of Bias Tool, and the methodological index for non-randomized studies (MINORS). The outcomes included Cobb angle, Angle of trunk rotation, Forced vital capacity, Forced expiratory volume in 1 second, and Quality of life. R 4.0.5 software was used, and standardized mean difference (SMD) and 95% confidence intervals (CI) were calculated for continuous outcomes, random model.Twenty-three studies were included. Depending on the outcome measured, the effect size of the different methods in the treatment of idiopathic scoliosis was from small to large as follows: Cobb angle (SMD = -0.43, p < 0.0001), ATR (SMD = -0.25, p = 0.06), FVC (SMD = 0.48, p = 0.03), FEV1 (SMD = 0.51, p = 0.004), and QoL (SMD = 0.95, p < 0.0001).Our meta-analysis indicates the positive effects of applying conservative methods based on therapeutic exercise on patients with idiopathic scoliosis.